Consistency management in database systems - Armen J. Asatryan (Изд-во НАН РА)
By its de¯nition, a database must serve as a faithful and incorruptible repository of data. Applications that consult the database expect a "warranty" that the database is supplying the correct values. This survey brie°y presents the approaches of integrity constraint management in database systems. It re°ects the various research activities in this ¯eld. We focus on central approaches, concepts, methods, and systems in this area.
Keywords: Mathematics; Computer software